2016
DOI: 10.1007/978-94-024-0867-6_16
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ageing on Warm Mix Asphalts with High Rates of Reclaimed Asphalt Pavement

Abstract: Within the framework of the European Project SUP&R ITN a PhD thesis is carried out to study the durability of the combination of high rates of reclaimed asphalt pavement and warm mix asphalt technologies. For this purpose the complex modulus and fatigue resistance of three different asphalt mixtures, including surfactant modified and foamed warm mix asphalts, combined with reclaimed asphalt pavement (RAP) has been studied. The extra value is given by the application of an ageing procedure based on the oxidatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…The three mixtures tested in this study exhibited different fatigue slopes, with the 0% RAB mix having the steepest fatigue life slope. Contrary to this investigation, a number of previous studies have reported that ageing will lead to steeper slopes [ 32 ], as well as the inclusion of RA, which will lead to similar results (50% RA) [ 33 ]. Other studies have reported similar slopes between all-virgin mixes and mixes containing RA (up to 40% RA) [ 12 , 34 ].…”
Section: Resultsmentioning
confidence: 67%
“…The three mixtures tested in this study exhibited different fatigue slopes, with the 0% RAB mix having the steepest fatigue life slope. Contrary to this investigation, a number of previous studies have reported that ageing will lead to steeper slopes [ 32 ], as well as the inclusion of RA, which will lead to similar results (50% RA) [ 33 ]. Other studies have reported similar slopes between all-virgin mixes and mixes containing RA (up to 40% RA) [ 12 , 34 ].…”
Section: Resultsmentioning
confidence: 67%
“…Today, there is considerable focus on the concept of "environmental protection and energy conservation", and low-carbon technology for asphalt pavement construction is gaining attention [33][34][35][36][37][38][39]. Therefore, low-carbon technologies are proposed based on the two types of carbon emissions, and mainly involve carbon emission reduction in terms of energy consumption and asphalt mixtures.…”
Section: Low-carbon Technology In the Construction Of Asphalt Pavementsmentioning
confidence: 99%